Implementasi Program Siaga Bencana Di Sekolah Menengah Pertama Pada Kawasan Rawan Bencana Gunung Merapi Kecamatan Kayu Aro Kerinci - Trina Febriani; Dasrizal Dasrizal; Rozana Eka Putri; Wibi Wijaya (Journal on Education, 2023)
This study aims to determine the level of knowledge of school residents, school policies, school community preparedness planning, and mobilization of school resources in the process of implementing the school disaster preparedness program. This research was conducted at SMP Negeri 35 Kerinci, Kayu Aro Barat District, Kerinci Regency, Jambi Province. Data collection techniques used are tests, interviews, questionnaires, observation, and documentation. Technical analysis of data using quantitative descriptive. The results showed, 1) the level of knowledge of the school community about disasters in dealing with the eruption of Mount Merapi was very good, 2) school policies that supported the disaster preparedness school program were considered poor with 40% of the sub-variables fulfilled, 3) school community preparedness planning in efforts to reduce and deal with the risk of Mount Merapi eruption including well with sub-variables fulfilled 88.89% and 4) mobilization of school resources in efforts to reduce disaster risk of Mount Merapi eruption including well with sub-variables fulfilled 85.71%.